Rhizosphere microbiome: Functional compensatory assembly for plant fitness - Xun, Weibing; Shao, Jiahui; Shen, Qirong; Zhang, Ruifu (Computational and structural biotechnology journal, 2021)
Environmental pressure to reduce our reliance on agrochemicals and the necessity to increase crop production in a sustainable way have made the rhizosphere microbiome an untapped resource for combating challenges to agricultural sustainability. In recent years, substantial efforts to characterize the structural and functional diversity of rhizosphere microbiomes of the model plant Arabidopsis thaliana and various crops have demonstrated their importance for plant fitness. However, the plant benefiting mechanisms of the rhizosphere microbiome as a whole community rather than as an individual rhizobacterium have only been revealed in recent years. The underlying principle dominating the assembly of the rhizosphere microbiome remains to be elucidated, and we are still struggling to harness the rhizosphere microbiome for agricultural sustainability. In this review, we summarize the recent progress of the driving factors shaping the rhizosphere microbiome and provide community-level mechanistic insights into the benefits that the rhizosphere microbiome has for plant fitness. We then propose the functional compensatory principle underlying rhizosphere microbiome assembly. Finally, we suggest future research efforts to explore the rhizosphere microbiome for agricultural sustainability.